2017
DOI: 10.1038/srep40355
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Sub-Microspheres Synthesized by Picosecond Pulsed Laser Melting in Liquids: Educt Size Effects

Abstract: Pulsed laser melting in liquid (PLML) has emerged as a facile approach to synthesize submicron spheres (SMSs) for various applications. Typically lasers with long pulse durations in the nanosecond regime are used. However, recent findings show that during melting the energy absorbed by the particle will be dissipated promptly after laser-matter interaction following the temperature decrease within tens of nanoseconds and hence limiting the efficiency of longer pulse widths. Here, the feasibility to utilize a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 70 publications
(89 reference statements)
0
38
0
1
Order By: Relevance
“…Besides, as shown in Figure f, the X‐ray diffraction (XRD) pattern with clear, shaped, strong peaks also indicates that Ge nanospheres have good crystallinity. These peaks are consistent with cubic structure (Fd3m) of Ge . Raman spectroscopy is commonly used to provide a fingerprint of the compound.…”
Section: Resultsmentioning
confidence: 76%
“…Besides, as shown in Figure f, the X‐ray diffraction (XRD) pattern with clear, shaped, strong peaks also indicates that Ge nanospheres have good crystallinity. These peaks are consistent with cubic structure (Fd3m) of Ge . Raman spectroscopy is commonly used to provide a fingerprint of the compound.…”
Section: Resultsmentioning
confidence: 76%
“…Laser ablation synthesis and fragmentation of colloids has emerged as as ynthesis route that combines ah igh level of versatility [1][2][3] with manufacturing flexibility. [4,5] This flexibility is not only related to the flexible designs pace consisting of laser parameters, [6] liquid properties, [7] and target composition, [6] but also to target shape [8] and target assembly.…”
Section: Introductionmentioning
confidence: 99%
“…LML is a technique that allows particle fusion to evolve into submicrospheres (SMSs) [66] and enables the particle/powder to be reshaped into SMSs . The mechanisms for LML have been summarized in ref.…”
Section: Lspc Techniquementioning
confidence: 99%
“…The selectable educt of LML includes LAL‐synthesized colloids, Chem NPs, or microscale powders . It is often considered that NP agglomeration is a prerequisite to achieve SMSs by LML, but the groups of Gökce and Liang showed that laser irradiation of nanocolloids in liquids can directly trigger particle growth without the need for particle agglomeration pretreatment. This phenomenon should benefit from the formation of laser‐induced bubbles and subsequent bubble‐collapse‐induced shockwaves, which push the particles into agglomeration .…”
Section: Lspc Techniquementioning
confidence: 99%
See 1 more Smart Citation